Tibial cementing in UKA: a three-dimensional analysis of the bone cement implant interface and the effect of bone lavage - Jäger, Sebastian; Seeger, Jörn Bengt; Schuld, Christian; Bitsch, Rudi G.; Clarius, Michael (The journal of arthroplasty, 2013)
Loosening is a common cause for revision in cemented UKA. In a cadaver study, we analyzed the three-dimensional cement distribution under the tibial implant and the effect of bone lavage (pulsed lavage, syringe lavage) on maximum cement penetration and penetration volume. Analyses were determined by performing bone cuts in medio-lateral direction and converting this data into a 3D model. Pulsed lavage led to an increased mean maximum cement penetration 5.79±2.63mm and penetration volume 6471.34±1156.43mm3 compared to syringe lavage 4.62±2.61mm, 5069.81±1177.09mm3 (P<0.001; P<0.001). Our results show a complete cement mantle for both investigated lavage techniques. Cleansing the cancellous tibial bone bed using pulsed lavage is more effective than conventional syringe lavage and leads to a deeper cement penetration and lager cement penetration volume under the tibial component.
Gesehen am 19.03.2021